Decision-Making by Healthcare Professionals in High-Risk Conditions - Trofimov, Andrii; Miliutina, Kateryna; Kolodych, Daria; Pustovyi, Serhii; Trofimova, Daria (International Journal of Criminology and Sociology, 2022)
The most important reserve for improving the efficiency of any institution or organization is to improve the quality of timely management decisions. The conditions of existence of societies (organizations and individuals) in the modern world are constantly and rapidly changing, that makes special demands on the individual decision maker. In the current situation of the global economic crisis, which is accompanied by changes in resource, environmental, political, legislative, industrial, living conditions, management issues become especially relevant and require improvement of their scientific basis. In connection with the above, the purpose of the work is to present the features of the development of socio-psychological traits identified in the empirical study, depending on the level of management occupied by the person, to optimize its functioning.